The long-term impact of folic acid in pregnancy on offspring DNA methylation: follow-up of the Aberdeen Folic Acid Supplementation Trial (AFAST). (12th March 2018) - Richmond, Rebecca C; Sharp, Gemma C; Herbert, Georgia; Atkinson, Charlotte; Taylor, Caroline; Bhattacharya, Sohinee; Campbell, Doris; Hall, Marion; Kazmi, Nabila; Gaunt, Tom; McArdle, Wendy; Ring, Susan; et al.
Abstract: Background: It has been proposed that maternal folic-acid supplement use may alter the DNA-methylation patterns of the offspring during the in-utero period, which could influence development and later-life health outcomes. Evidence from human studies suggests a role for prenatal folate levels in influencing DNA methylation in early life, but this has not been extended to consider persistent effects into adulthood. Methods: To better elucidate the long-term impact of maternal folic acid in pregnancy on DNA methylation in offspring, we carried out an epigenome-wide association study (EWAS) nested within the Aberdeen Folic Acid Supplementation Trial (AFAST—a trial of two different doses: 0.2 and 5 mg, folic acid vs placebo). Offspring of the AFAST participants were recruited at a mean age of 47 years and saliva samples were profiled on the Illumina Infinium Human Methylation450 array. Both single-site and differentially methylated region analyses were performed. Results: We found an association at cg09112514 ( p  = 4.03×10 –9 ), a CpG located in the 5' untranslated region of PDGFRA, in the main analysis comparing the intervention arms [low- (0.2 mg) and high-dose (5 mg) folic acid combined ( N  = 43)] vs placebo ( N  = 43). Furthermore, a dose–response reduction in methylation at this site was identified in relation to the intervention. In the regional approach, we identified 46 regions of the genome that were differentially methylated in response to the intervention (Sidak p-value <0.05), including HLA-DPB2, HLA-DPB1, PAX8 and VTRNA2–1 . Whereas cg09112514 did not replicate in an independent EWAS of maternal plasma folate, there was suggested replication of differential methylation in PAX8 . Conclusions: The results of this study suggest that maternal folic-acid supplement use is associated with changes in the DNA methylation of the offspring that persist for many years after exposure in utero . These methylation changes are located in genes implicated in embryonic development, immune response and cellular proliferation. Further work to investigate whether these epigenetic changes translate into detectable phenotypic differences is required.